Perbandingan Kuat Tekan pada Beton SCC Menggunakan Bahan Zat Aditif yang Bersifat Accelerator dan Retarder dengan Metode Destructive Test - Ernadi Zamzami; Hariyadi Hariyadi; Maya Saridewi Pascanawaty (Jurnal Talenta Sipil, 2026)
The ever-evolving construction industry demands innovation in high-quality, economical, and efficient concrete materials. Self-Compacting Concrete (SCC) is one solution due to its self-compacting ability. However, extreme conditions often affect the setting and hardening time of concrete, requiring the use of additives in the form of accelerators to accelerate or retarders to slow down the setting time. This study aims to analyze and compare the compressive strength values of SCC concrete using accelerator and retarder additives through a destructive test method. This study was conducted at the Civil Engineering Laboratory of the University of Muhammadiyah Mataram. The test specimens used were concrete cylinders measuring 15 cm x 30 cm with a design compressive strength of f’c = 20 MPa and an additive dosage of 0.5%. Fresh concrete characteristics testing included slump flow, J-ring, and sieved stability index. The compressive strength testing of hardened concrete was carried out using a Compression Testing Machine (CTM) at the ages of 7, 14, 21, and 28 days. The test results showed that the material and fresh concrete had met all the eligibility criteria for SCC concrete, with a slump flow distribution value of 65 cm, J-ring 67 cm, and a sieve stability index of 17.52%. The use of accelerator additives proved to be the most effective in increasing early strength and producing the highest compressive strength of 24,84 MPa on the 28th day. The use of retarder produced a compressive strength below normal concrete at the age of 7 days (14.60 MPa compared to 15.56 MPa), but showed a better increase in strength at the age of 28 days. Overall, the choice of additive type must be adjusted to the needs, accelerator is effective in accelerating hardening, while retarder is more suitable for improving long-term workability.